Future Elementary School Teachers' Conceptual Change Concerning Photosynthesis - Ahopelto I; Mikkila-Erdmann M; Anto E; Penttinen M (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The purpose of this study was to examine conceptual change among future elementary school teachers while studying a scientific text concerning photosynthesis. Students' learning goals in relation to their learning outcomes were also examined. The participants were future elementary school teachers. The design consisted of pre- and post-tests. The study revealed that student teachers have severe misconceptions concerning photosynthesis. However, the results indicated that a coherent expository text works as an effective support in the learning process. Further, results showed that students who express high-level learning goals are more likely to undergo conceptual change than students with low-level learning goals. The study highlights the importance of science education in teacher training at universities.